PERAN PENDIDIKAN FORMAL DAN KONSEP DIRI TERHADAP POTENSI KEWIRAUSAHAAN MAHASISWA - zulia khairani (Jurnal Ilmiah Ekonomi Dan Bisnis, 2018)
In the midst of the high number of employee deductions made by many companies at this time, it is very necessary for the younger generation to have the ability to entrepreneurship so as to be able to run their business independently. This study aims to identify the role of formal education, self-concept, and its effect on entrepreneurship potential in students. The population in this study is a student of Faculty of Economics, University of Lancang Kuning. Methods of data retrieval using an online questionnaire. Data processing uses quantitative analysis through descriptive analysis, multiple regression analysis, and hypothesis testing with t-test and F-test. Qualitative analysis is done by interpretation of the data obtained in the research and the results of data processing that has been implemented by giving information and explanation. The results of descriptive data indicate that formal education, self-concept, and entrepreneurship potential of students of faculty of economics management study program in good criterion. Formal education and self-concept positively and significantly affect the entrepreneurial potential of students. This means that improvements in the quality of formal education and self-concept will increase the potential of entrepreneurship in students